Cross-talk between ethylene and drought signalling pathways is mediated by the sunflower Hahb-4 transcription factor - Manavella, Pablo Andrés (2006)
Hahb-4 is a member of the Helianthusannuus (sunflower) subfamily I of HD-Zip proteins that is transcriptionally regulated by water availability and abscisic acid. Transgenic Arabidopsis thaliana plants overexpressing this transcription factor (TF) exhibit a characteristic phenotype that includes a strong tolerance to water stress. Here we show that this TF is a new component of ethylene signalling pathways, and that it induces a marked delay in senescence. Plants overexpressing Hahb-4 are less sensitive to external ethylene, enter the senescence pathway later and do not show the typical triple response. Furthermore, transgenic plants expressing this gene under the control of its own inducible promoter showed an inverse correlation between ethylene sensitivity and Hahb-4 levels. Potential targets of Hahb-4 were identified by comparing the transcriptome of Hahb-4-transformed and wild-type plants using microarrays and quantitative RT-PCR. Expression of this TF has a major repressive effect on genes related to ethylene synthesis, such as ACO and SAM, and on genes related to ethylene signalling, such as ERF2 and ERF5. Expression studies in sunflower indicate that Hahb-4 transcript levels are elevated in mature/senescent leaves. Expression of Hahb-4 is induced by ethylene, concomitantly with several genes homologous to the targets identified in the transcriptome analysis (HA-ACOa and HA-ACOb). Transient transformation of sunflower leaves demonstrated the action of Hahb-4 in the regulation of ethylene-related genes. We propose that Hahb-4 is involved in a novel conserved mechanism related to ethylene-mediated senescence that functions to improve desiccation tolerance.